The Reality of Person-Environment Fit in the Public Hospitals in Taif: An Empirical Study - Alharbi, Abdullah (The Arab Journal of Administration, 2023)
The study aimed to describe the person-environment fit in the public hospitals in Taif governorate by diagnosing the levels of fit (Person-Job Fit, Person-Supervisor Fit, Person-Group Fit, Person-Organization Fit), and analyzing to what extent the views of employees working in these hospitals differ regarding levels of fit. To meet the study’s aims, descriptive and analytical approach was used, and a questionnaire was developed, which consisted of 42 items reflecting the above four main dimensions. The target population comprised all employees of the public hospitals in Taif Governorate, and 360 employees were selected according to the stratified random sampling method. The appropriate statistical tests were employed to achieve the study objectives. The study revealed that person-environment fit and its dimensions in the public hospitals in Taif Governorate were high, and the scores on the subdimensions ranged from high to medium. However, needs-supply fit in terms of training, career development, social activities, the financial compensation they received, and employees’ pride in their current jobs did not exceed the medium level. Also, the results revealed statistically significant differences in the responses of the sample towards person-environment fit and its different levels, associated with respondents’ gender, age, employers, and jobs. However, there were no statistically significant differences in their responses to these dimensions related to their nationalities, work experience, and education. Finally, the study concluded with a number of scientific and practical recommendations.